Tempat Pengendalian Emosi Negatif - Abdul Aziz Ali Rosyiddin; Nur Aziz Affandi; Rini Risnawita; Yuli Darwati (Gunung Djati Conference Series, 2023)
This study aims to discuss various places that are often used to control negative emotions. This study uses a quantitative approach by applying descriptive methods. The results of the research and discussion show that there are places to control negative emotions that are mostly chosen by the subjects, namely, home, place of girlfriends, and places of friends from 3 subject categories namely, early adulthood, single, and dating. This study concluded that the place chosen by most of the subjects was a place where they felt comfortable and safe to control their negative emotions. Especially for the house it is possible for other people not to know what negative emotions are being controlled by the subject.